Biomehanika kolčnega sklepa - Vengust, Rok (Medicinski razgledi, 1997)
Biomechanics of the hip joint is a discipline which deals with loads and stresses exerted on the hip joint surface. It provides an insight into the pathogenesis of some hip disorders and enables the clinician to plan correct treatment. The paper presents a biomechanical analysis of the one-legged stance, and investigates the factors influencing hip joint stresses. Some examples are included to illustrate the application of biomechanical principles to orthopaedic practice.
Keywords: kolčni sklep; biomehanika; ortopedija